Fabrication of Adsorber Bed Apparatus for dehydration of ethanol on Zeolite based media - Abdeen, Fouad R. H.
The recent increase of fuel oil price has oriented researchers towards producing fuel ethanol from biomass materials. The main challenge encountered in such production process is the removal of large excess amount of water within the produced ethanol. Distillation, though is an energy extensive process, is usually used to produce ethanol up to 95% purity. Production of higher purity ethanol is usually a major challenge due to the formation of an azeotrope. In this study, a small adsorber bed apparatus is constructed and used to purify ethanol up to 99.5%. The apparatus consists of fluid delivery system, adsorber bed subsystem, and storage and sampling unit. The adsorber bed subsystem of this apparatus consists of a packed bed column where molecular sieves like zeolite can be packed. The apparatus is designed to be packed and repacked several times and with various types of zeolites. Nevertheless, this study focuses on using 3A zeolite molecular sieves for adsorbing water out of ethanol. 3A zeolites are proven to be efficient in removal of water from ethanol-water azeotrope since their pore size is less than 0.3nm which allows only water to adsorb to the inner large surface area of zeolite. The overall process has resulted in the production of ethanol of purity higher than 99.5%. The success achieved in this small adsorber bed system makes it possible and profitable to scale it up for larger production